Growth and yield of cucumber and tilapia fish in aquaponics under UAE climatic condition - Radhakrishnan Subramanian; Ibrahim Belal (Innovations in Agriculture)
The healthiest and most effective method of producing food is aquaponics, particularly in arid regions. In comparison to conventional crop production, aquaponics uses less than 90% of the water, produces crops that grow more quickly, and does not employ pesticides. With an average weight of 17g, fish Oreochromis niloticus tanks were stocked with 120 fish per m2. Three times per day, Nile tilapia were fed a floating commercial tilapia diet until they were full. Three cucumber plants were planted per square meter in plant culture raceways. Water, feed, and electricity usage are all tracked in aquaponics systems. The growth characteristics and monthly production of the fish and cucumber were noted. Environmental aspects of the system, including light intensity, temperature, and water quality parameters, were assessed. Six months were spent conducting the experiment in a two-time cultivation. Three months were needed from one seedling to harvest; the first month was spent growing and flowering the plant, and the second and third months were used to harvest the cucumbers. With an input of 992.67 tons of feed, 12110.13 K.Wh of electricity, and 59.20 m3 of water consumption, each aquaponics system produced on average 3.2 tons of cucumber in a 120 m2 area and 0.5 tons of fish in a 15 m3 area.